PENGARUH KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA AFIFAH MAKE UP - Nurlaela, Siti Alifiya; Suherman, Enjang; Khalida, Laras Ratu (Universitas Respati Indonesia, 2025)
This research examines how service quality and pricing perception affect Afifah Makeup purchases. In early 2024, internal restrictions caused a severe reduction in service and price-influenced purchase choices. This quantitative research uses multiple linear regression. Purposive sampling chose 111 clients who had utilized the service at least once for the study. SPSS 15 analyzed Likert scale questionnaire data. The findings revealed that service quality and pricing influenced perception purchases. Price dominates perception of service quality, with a regression coefficient of 0.731 against 0.263. The R Square score of 0.892 shows that these two factors explain 89.2% of purchase choices. This survey suggests Afifah Makeup enhance service and pricing transparency to attract more clients.